38-year-old woman in labor with concomitant ST elevation myocardial infarction treated with primary coronary angioplasty: A case report - Gawinski, Łukasz; Matewski, Karol; Tomczak, Ernest; Szymański, Paweł; Sadłecki, Paweł; Kozłowski, Remigiusz (Nursing Problems / Problemy Pielęgniarstwa, 2025)
Myocardial infarction (MI) is extremely rare during pregnancy and postpartum period; it is even less common in clinical practice during labor. Currently, there are no clear guidelines for the management of such complicated clinical cases. In this paper, a case of a 38-year-old multiparous woman with anterior wall ST elevation MI in the first stage of labor was presented. The patient underwent an emergency caesarean section without complications, delivering a full-term live son. The patient was transferred to catheterization laboratory for coronary angiography with primary coronary intervention (PCI) of the left anterior descending artery. During 18 months of follow-up, the mother had no recurrence of stenocardial symptoms, complications of antiplatelet therapy, or signs of worsening heart failure. The approach adopted by the authors of this report seems to be an effective and completely safe method of management in such complicated clinical scenarios.